Answer:
Let the present age of the man be x years.
Age of the man 15 years ago =(x−15) years and
Age of the man 15 years later =(x+15) years
According to the given condition, we have
(x+15)=2(x−15)
⇒x+15=2x−30
⇒x−2x=−30−15
⇒−x=−45 or x=45 years
Hence, the present age of the man is 45 years.
Step-by-step explanation:
Hope it helps you..
Your welcome in advance..
(◍•ᴗ•◍)
Answer:
35
Step-by-step explanation:
base × height so just multiple 7 and 5
Answer:
888970994
Step-by-step explanation:
99393 * 17888 = 1777941984
1777941984/2 = 888970992
888970992+2 = 888970994
Answer:
start witg parentecees, then multiplication then addind and substracting
Step-by-step explanation:
2(x+10)+10-4+5 = 2x + 20 +10 -4 +5
2x+31 is the final answer